THE EFFECTIVENESS OF THE COOPERATIVE LEARNING STRATEGY IN DEVELOPING CRITICAL READING SKILLS AMONG FIRST-YEAR STUDENTS AT THE COLLEGE OF LAW - Yusra Nayef Nouri Al-Dakhili (PT. Antis International Publisher, 2026)
Objective: This study aims to identify the effectiveness of the cooperative learning strategy in developing critical reading skills among first-year students at the College of Law, Al-Ayen Iraqi University. Method: Cooperative learning is considered a modern teaching strategy based on positive interaction, organized group work, role distribution, and participatory knowledge construction. The study adopted a quasi-experimental design with two equivalent groups: an experimental group taught through cooperative learning and a control group taught through the traditional method. The sample consisted of 350 first-year law students, including 200 males and 150 females. The sample was divided into two groups: the experimental group, which studied according to the cooperative learning strategy, and the control group, which studied according to the traditional method. The researcher prepared a critical reading skills test that measured the ability to analyze ideas, distinguish facts from opinions, infer implicit meanings, evaluate arguments and evidence, identify fallacies, and formulate critical judgments. The validity of the test was verified through expert judgment, and its reliability was verified using Cronbach’s alpha. Results: The results showed statistically significant differences at the 0.05 level in favor of the experimental group in the post-test, with a large effect size. This indicates the effectiveness of the cooperative learning strategy in developing critical reading skills among law students. Novelty: Cooperative learning is considered a modern teaching strategy based on positive interaction, organized group work, role distribution, and participatory knowledge construction. This study aims to identify the effectiveness of the cooperative learning strategy in developing critical reading skills among first-year students at the College of Law, Al-Ayen Iraqi University. In light of these results, the study recommends adopting this strategy in higher education, especially in courses that require text analysis, interpretation, and evaluation.